2023
DOI: 10.1002/smtd.202300197
|View full text |Cite
|
Sign up to set email alerts
|

V4C3 MXene Immune Profiling and Modulation of T Cell‐Dendritic Cell Function and Interaction

Laura Fusco,
Arianna Gazzi,
Christopher E. Shuck
et al.

Abstract: Although vanadium‐based metallodrugs are recently explored for their effective anti‐inflammatory activity, they frequently cause undesired side effects. Among 2D nanomaterials, transition metal carbides (MXenes) have received substantial attention for their promise as biomedical platforms. It is hypothesized that vanadium immune properties can be extended to MXene compounds. Therefore, vanadium carbide MXene (V4C3) is synthetized, evaluating its biocompatibility and intrinsic immunomodulatory effects. By combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Most recently, Fusco et al. investigated the impact of V 4 C 3 nanosheets on DCs as well as the interaction between T cell and DC with Ti 3 C 2 as a reference material [199] . Results demonstrated that V 4 C 3 induced a significant decrease in CD69 and CD25 activation markers and strongly inhibited LPS‐induced increase in key proinflammatory cytokines.…”
Section: Nano‐bio Interactions Between 2d Nanomaterials and Mps Cellsmentioning
confidence: 99%
“…Most recently, Fusco et al. investigated the impact of V 4 C 3 nanosheets on DCs as well as the interaction between T cell and DC with Ti 3 C 2 as a reference material [199] . Results demonstrated that V 4 C 3 induced a significant decrease in CD69 and CD25 activation markers and strongly inhibited LPS‐induced increase in key proinflammatory cytokines.…”
Section: Nano‐bio Interactions Between 2d Nanomaterials and Mps Cellsmentioning
confidence: 99%
“…29 Vanadium carbide (V 2 C) nanosheets, one type of MXene, were first used in the biomedical field in 2019. 30 As a member of the MXene family, V 2 C nanosheets have great biocompatibility 31 and can be biodegraded by enzymes. In addition to their large specific surface area, hydrophilicity, and high biocompatibility, which are common to conventional MXene materials, V 2 C nanosheets are also light-responsive nanoagents 32 and show strong absorption in the near-infrared region.…”
mentioning
confidence: 99%